A New Subclass of Multivalent Function Defined by Using Jackson Derivative Operator (Global Journal of Science Frontier Research, 2023)
In this paper the authors have used Jackson Derivative operator to form a new subclass of multivalent function and derived some results for a function belonging to new subclass of multivalent functions. The main emphasis is on coefficient estimate of functions belonging to new subclass of multivalent function, the radii of starlikeness, convexity and close to convexity properties of a function have also been discussed. The results reduces to the earlier known results of Silverman, Srivastava, Altintas and Khosravianarab by assuming some particular values of the parameters.
Keywords: jackson derivative operator; multivalent functions; coefficient estimate; radii of starlikeness